Flickors och pojkars lek i dockvrå och dockskåp: Normativa förväntningar och hierarkier i förskolan vid mitten av 1900-talet - Sara Backman Prytz; Josefin Forsberg Koel (Nordic Journal of Educational History, 2023)
Girls’ and boys’ play in the home corner and doll house: Gendered expectations and hierarchies in Swedish preschool in the middle of the 20th century. This article examines children’s play in a gender stereotypical framing: the home corner and dollhouses in mid-1900’s Swedish preschool. Three different types of empirical material were analysed: a preschool teachers’ questionnaire, observation protocols from children’s play with dollhouses and complementary photographs of playing preschool children. By examining these, we have been able to identify the preschool teacher’s gender stereotyped expectations of girls’ and boys’ play and how gender stereotyped expectations of children were maintained. The children especially helped to uphold a dichotomy between girls’ and boys’ play. This dichotomy was confirmed by the fact that girls had a hierarchically superior role in the game when both girls and boys participated. Boys, on the other hand, had more space for action in the gender-stereotypically framed play, as they were not bound by play conventions in the same way as girls. Boys’ attempts at nurturing play with dolls, i.e. more femininely coded play, was disparaged by educators and other children.